Relationship between higher estrus-associated temperatures and the bovine preovulatory follicular fluid metabolome - Pollock, Abigayle B.; Moorey, Sarah E.; Hessock, Emma A.; Klabnik, Jessica L.; Payton, Rebecca R.; Schrick, F. Neal; Campagna, Shawn R.; Edwards, J. Lannett (Frontiers in Animal Science, 2023)
Objective was to examine relationship between HEAT and the preovulatory follicular fluid metabolome. It was hypothesized to test hypothesis-that HEAT is is functionally important to affect fertility-related components in the preovulatory follicle.Methods: Estrus was synchronized in nonlactating Jersey cows. using 7-day CIDR protocol. Thermochron iButton temperature data logger was affixed to blank CIDR and intravaginally inserted after CIDR removal. Follicular fluid was aspirated 14.9 + 3.3 h after an animal first stood to be mounted. Eighty-six metabolites were identified in follicular fluid samples from cows with varying levels of HEAT. Mixed modelR regression models wereas performed using metabolite abundance and HEAT variables. Best fit models were determined using backwards manual selection (P < 0.05).Eighty-six metabolites were identified in cow follicular fluid samples. from cows with varying levels of HEAT. Vaginal temperature at first mount and when it was expressed as a, change from baseline, was positively related to the abundance of 20 4 metabolites (taurine, sn-glycerol 3phosphate, glycine, cysteine), and negatively related to 1 metabolite (serine). Enriched pathways included 'Aminoacyl-tRNA biosynthesis', 'Phenylalanine, tyrosine, and tryptophan biosynthesis', 'Thiamine metabolism', 'Glutathione metabolism', 'Taurine and hypotaurine metabolism', 'Pyrimidine metabolism', and 'Phenylalanine metabolism' (FDR < 0.1). Vaginal temperature at first standing mount was related to the differential abundance of two metabolites (jJasmonate, N-cCarbamoyl-Laspartate). Three metabolites were related to maximum vaginal temperature (N-cCarbamoyl-Laspartate, uUracil, gGlycodeoxycholate). When expressed as a change from baseline, maximum vaginal temperature was related to differential abundance of uUracil, uUric aAcid, 6-pPhospho-Dgluconate. The time to maximum vaginal temperature was related to N-cCarbamoyl-L-aspartate, gGlycodeoxycholate, jJasmonate, and tTricarballylic aAcid. Pertaining to the combination of HEAT and its duration, area under the curve from first initial vaginal temperature increase to maximum vaginal temperature related to 6-pPhospho-D-gluconate, sSulfolactate, gGuanidoacetic aAcid, and aAspartate. Area under the curve from initial vaginal temperature increase and up to 10 h after a cow first stood to be mounted or when cow temperature returned to baseline related to the differential abundance of uUracil, sn-gGlycerol 3-pPhosphate, mMethionine sSulfoxide, and tTaurodeoxycholate.